Can AI Predict Frailty in Older Adults? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2021)
Frailty is a complex and significant geriatric syndrome characterized by a state of increased vulnerability to adverse health outcomes, including falls, hosp...
Keywords: AI in Geriatrics; Predict; Frailty; Older; Artificial Intelligence; Machine Learning